THE ROLE OF CLASSROOM INTERACTION IN STUDENTS’ SPEAKING SKILL (A Case Study Research In Senior High School) - Larasaty, Gita; Yutinih, Yutinih (Fakultas Keguruan dan Ilmu Pendidikan, Program Studi Pendidikan Bahasa Inggris, 2018)
This study is aimed at finding out how the role of classroom interaction in students’ speaking skill by showing the role of student-student interaction and student-teacher interaction inside classroom. While, the students often found some problems in learning speaking; one of the problem that they faced was lack of interaction in classroom. According to Warda (2015:2) “lack of interaction in EFL classes, could be the first lead to student’s oral poor productions.” Allwright (1984:156) defined interaction as the fundamental fact of classroom pedagogy- the fact that everything that happens in the classroom happens through a process of live-person-to-person interaction. Classroom interaction then is the one of facilitator to start conversation, as Nunan (1991:50) argued in two-way tasks (conversational interaction), all participants have a piece of informational known only to them which must be contributed to the small group discussion for the task to be completed successfully. The writer used qualitative research design and took one of the kinds of qualitative research method, which is a case study. The data obtained from the triangulation instruments. The first instrument was observation, this instrument helped the writer to find out the real situation in classroom especially the students’ interaction in speaking class, the second instrument was questionnaire, this instrument was to classify and determine how frequently interaction in classroom, the third instrument was the data transcript from interview. The results show that 92% of the students are aware about the important of classroom interaction in their speaking skill and 56% of them need their teacher to be guider as well as motivator with the number 24% to encourage them to interact and speak in the classroom. And students really need the teacher to provide more opportunities to interact with her, which according to their responses 68% of them prefer student-teacher interaction the most. In fact, students seem to know one of good students’ qualities is speaking and interacting in classroom, since refraining classroom interaction and showing no interest will naturally affect their speaking ability.